Integration of Renewable Energy Sources into Power Systems in Nigeria for Operational Efficiency - Sunday, Philip; Mutah, Waziri Mallam (Lembaga Yasin AlSys, 2025)
This study investigates the integration of renewable energy sources (RES) into Nigeria’s power systems to enhance operational efficiency. Nigeria’s power sector has long been plagued by challenges such as inadequate infrastructure, frequent outages, and an inability to meet energy demands. The integration of renewable energy, particularly solar and wind, offers a potential solution to improve the reliability and efficiency of the national grid. A descriptive survey research design was adopted, with data collected from key stakeholders in the power sector, including administrators, technical experts, and energy consumers. The study revealed that the integration of RES, supported by technological innovations such as smart grids and energy storage systems, can significantly improve operational efficiency. However, barriers such as insufficient funding, regulatory hurdles, and public acceptance were identified as key challenges. The study concludes that modernizing infrastructure, fostering technological innovation, and developing supportive regulatory frameworks are crucial for the successful integration of RES into Nigeria’s power systems. The findings provide insights for policymakers and industry stakeholders to drive Nigeria’s energy transition toward a more sustainable and efficient future.